Sex- and Tissue-Specific Expression Profiles of Odorant Binding Protein and Chemosensory Protein Genes in Bradysia odoriphaga (Diptera: Sciaridae) - Zhao, Yunhe; Ding, Jinfeng; Zhang, Zhengqun; Liu, Feng; Zhou, Chenggang; Mu, Wei (Frontiers in Physiology, 2018)
Bradysia odoriphaga is an agricultural pest insect affecting the production of Chinese chive and other liliaceous vegetables in China, and it is significantly attracted by sex pheromones and the volatiles derived from host plants. Despite verification of this chemosensory behavior, however, it is still unknown how B. odoriphaga recognizes these volatile compounds on the molecular level. Many of odorant binding proteins (OBPs) and chemosensory proteins (CSPs) play crucial roles in olfactory perception. Here, we identified 49 OBP and 5 CSP genes from the antennae and body transcriptomes of female and male adults of B. odoriphaga, respectively. Sequence alignment and phylogenetic analysis among Dipteran OBPs and CSPs were analyzed. The sex- and tissue-specific expression profiles of 54 putative chemosensory genes among different tissues were investigated by quantitative real-time PCR (qRT-PCR). qRT-PCR analysis results suggested that 22 OBP and 3 CSP genes were enriched in the antennae, indicating they might be essential for detection of general odorants and pheromones. Among these antennae-enriched genes, 9 OBPs (BodoOBP2/4/6/8/12/13/20/28/33) were enriched in the male antennae and may play crucial roles in the detection of sex pheromones. Moreover, some OBP and CSP genes were enriched in non-antennae tissues, such as in the legs (BodoOBP3/9/19/21/34/35/38/39/45 and BodoCSP1), wings (BodoOBP17/30/32/37/44), abdomens and thoraxes (BodoOBP29/36), and heads (BodoOBP14/23/31 and BodoCSP2), suggesting that these genes might be involved in olfactory, gustatory or other physiological processes. Our findings provide a starting point to facilitate functional research of these chemosensory genes in B. odoriphaga at the molecular level.